2000
DOI: 10.1128/iai.68.5.2663-2670.2000
|View full text |Cite
|
Sign up to set email alerts
|

Eradication ofCryptosporidium parvumInfection by Mice with Ovalbumin-Specific T Cells

Abstract: CD154 is necessary for mice to clear a Cryptosporidium parvum infection, but whether this ligand has to be expressed on T cells with specificity for C. parvum has not been determined. We infected DO11.10 (ovalbumin specific) T-cell receptor transgenic mice that had been bred to a RAG ؊/؊ background with C. parvum and found that the infection was cleared within 6 weeks, while RAG ؊/؊ controls were unable to clear C. parvum infection. Recovery was accompanied by an increase in the number of splenic T cells with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…It was previously shown that CD4 T cells expressing a transgene for an ovalbumin-specific antigen receptor sufficed to clear C. parvum infection from SCID mice, provided that the transgenic T cells became activated and were able to express CD154 (23). This result suggested that the clearance of C. parvum required an interaction between CD154 (presumably expressed on an activated T cell) and CD40.…”
mentioning
confidence: 61%
See 3 more Smart Citations
“…It was previously shown that CD4 T cells expressing a transgene for an ovalbumin-specific antigen receptor sufficed to clear C. parvum infection from SCID mice, provided that the transgenic T cells became activated and were able to express CD154 (23). This result suggested that the clearance of C. parvum required an interaction between CD154 (presumably expressed on an activated T cell) and CD40.…”
mentioning
confidence: 61%
“…Certainly CD8 T cells and MHC-I antigens do not seem to be required for cryptosporidia to be cleared (1,28). Even the CD4 T-cell response that can clear a C. parvum infection is unusual in that the specificity of the T-cell receptor seems less important than the activation of the T cells and their utilization of an intact CD154-CD40 signaling pathway (23). CD40 ligation can lead to apoptosis of fibroblasts (20) and, in vitro, of C. parvuminfected cells (17,30), so the direct triggering of apoptosis in CD40 ϩ infected cells by CD154 expressed on activated T cells was considered a potential mechanism that could account for the contribution of CD40 to C. parvum immunity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of animal models have been used to study the nature and role of host immune responses to C. parvum infection, including neonatal mice (22), dexamethasonetreated mice (54), congenital immunodeficient (nude, RAG Ϫ/Ϫ , SCID) mice (1,28,33), and mice with targeted gene mutations for major histocompatibility complex class II, CD40, IFN-␥ or T-cell receptor ␣ (2, 19, 22, 50). From the studies performed with these models, the central importance of CD4 ϩ T cells (chronic) and IFN-␥ (acute and chronic) in the resistance to and recovery of animals from C. parvum infection have been proven.…”
Section: Discussionmentioning
confidence: 99%